Epizootic Activity of Natural Plague Foci in the Territory of the Russian Federation in 2011, and Prognosis for 2012 - N. V. Popov; V. E. Bezsmertny; A. N. Matrosov; A. A. Kuznetsov; T. V. Knyzeva; V. P. Popov; D. B. Verzhutsky; L. S. Nemchenko; L. D. Shilova; V. M. Dubyansky; O. V. Maletskaya; V. P. Toporkov; et al. (Проблемы особо опасных инфекций, 2012)
Carried out is the assessment of epizootic activity of natural plague foci in the Russian Federation and in the Republic of Kazakhstan during the period of 2000-2010. It is specified that 38 plague microbe strains have been isolated in the territory of the Russian Federation, the total area of epizooties being 882,5 km2. Plague microbe strains are isolated in the territory of East-Caucasian high-mountain and Altai mountain natural foci. Identified are the reasons of low epizootic activity of plain and low-mountain natural plague foci in the Russian Federation. Outlined is the role of climatic factors in the development of current intense depression in numbers of carriers and vectors of plague. Put forward is the prognosis on the low epizootic activity of the natural plague foci in the Russian Federation in 2012. It is substantiated that the emergence of local epizooties in 2012 is to take place in the territory of Altai mountain, Tuvin mountain and East-Caucasian high-mountain natural plague foci.